2017
DOI: 10.1371/journal.pone.0183348
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the incidence of pneumonia, bacterial meningitis, and infant mortality 5 years following introduction of the 13-valent pneumococcal conjugate vaccine in a "3+0" schedule

Abstract: BackgroundStreptococcus pneumoniae causes about 826,000 deaths of children in the world each year and many health facility visits. To reduce the burden of pneumococcal disease, many nations have added pneumococcal conjugate vaccines to their national immunization schedules. Nicaragua was the first country eligible for GAVI Alliance funding to introduce the 13-valent pneumococcal conjugate vaccine (PCV13) in 2010, provided to infants at 2, 4, and 6 months of age. The goal of this study was to evaluate the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Our index elaborated on the individual vaccine coverage trends by demonstrating an overall commitment across emerging economies towards increasing vaccine access. Our findings indicating a broader public health value of vaccine commitment are supported by previous studies reporting decreased infant mortality after PCV13, influenza, meningococcal, and rotavirus vaccines; [21][22][23][24] however, the relationship between individual vaccination policies and life expectancy has been investigated to a lesser extent. In addition, the broader value of vaccine commitment was also demonstrated in a recent study suggesting an increase in GDP per dollar invested in vaccines, likely due in part to the impact of vaccines on disease prevention and infant survival, enabling a more productive work force.…”
Section: Discussionsupporting
confidence: 86%
“…Our index elaborated on the individual vaccine coverage trends by demonstrating an overall commitment across emerging economies towards increasing vaccine access. Our findings indicating a broader public health value of vaccine commitment are supported by previous studies reporting decreased infant mortality after PCV13, influenza, meningococcal, and rotavirus vaccines; [21][22][23][24] however, the relationship between individual vaccination policies and life expectancy has been investigated to a lesser extent. In addition, the broader value of vaccine commitment was also demonstrated in a recent study suggesting an increase in GDP per dollar invested in vaccines, likely due in part to the impact of vaccines on disease prevention and infant survival, enabling a more productive work force.…”
Section: Discussionsupporting
confidence: 86%
“…The pneumococcal conjugate vaccine (PCV) has potential to greatly reduce childhood mortality. Most assessments of PCV impact on all-cause pneumonia mortality were performed in Latin American and Caribbean countries, with results ranging from no reduction in children <5 years in Brazil, to a 44% reduction in children <1 year in Peru for all-cause pneumonia mortality [ 3 6 ]. Data are lacking from Africa, including South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Nicaragua reported declines of 33% (20-43%) (27) in all-cause mortality in infants 1-11 months two years after vaccine introduction. A similar study conducted in Nicaragua four years after PCV introduction found an even higher all-cause mortality decline among 1-11 month olds, of 44% (23-59%) (28). However, LRI mortality was estimated to represent less than a third of total deaths in that age group (11).…”
Section: Discussionmentioning
confidence: 94%